Development of ternary squaraine-tryptamine-nitroaromatic charge-transfer complexes for potential use as colorimetric stains in gel electrophoresis. (October 2015) - Lynch, Daniel E.; Cox, Martin; Smith, Graham
Abstract: A water-soluble dual pendant squaraine with tryptaminium cations has been prepared and mixed with dinitroaromatics (3, 5-dinitrobenzoic acid, 3, 5-dinitrosalicylic acid, and 2, 4-dinitrophenol) in solution to create ternary complexes containing indole-nitroaromatic charge-transfer pairs. Examination of the X-ray crystal structures of just the three types of charge-transfer complexes, without the squaraine moiety, employed yielded six structures in which all bar one demonstrated charge-transfer pair or stacking associations between the indole and nitroaromatic rings. These charge-transfer associations were evident in the UV–visible absorption spectra of each complex, including those incorporating the squaraine. Examination of the fluorescence performance upon illumination with 300 nm light of each complex, particularly in the presence of an equimolar amount of protein, showed that although there was a ten-fold increase in the fluorescence of the squaraine moiety (above that without protein) the levels across the series were no more than that observed for the base bistryptaminium squaraine. Graphical abstract: Highlights: Synthesis of bistryptaminium dual-sulfonate bis(indolenine)squaraine salt. Solution preparation of ternary squaraine-tryptamine-nitroaromatic complex. Ternary complexes indicate charge-transfer interactions, measured by UV–vis. No enhanced fluorescence (above that of other squaraines) in protein solutions. X-ray crystal structures of six tryptamine charge-transfer salts are reported.